Effects of betaine-rich nano fertilizer on chemical properties of salt-stressed sweetcorn (Z. mays var saccharata) and A. thaliana - Nur Fatihah, Hasan Nudin; Mohammad Moneruzzaman, Khandaker; Nadiawati, Alias (2021)
Climate change is causing salt stress that is detrimental to crop ecosystems including lowering nutrient availability and affecting crop growth and production. Moreover, the salt stressed soil induces physiological disorder and chemical properties in plants which influence the growth and development of plants. Therefore, the aim of this study was to examine the effects of betaine-rich Nano fertilizer (B1N1) on chemical properties of salt-stressed sweet corn (Z. mays var. saccharata) and A. thaliana under salt stress. In this study, plants were grown in a controlled plant growth room. Different salinity levels (S0: 0 dS/m, S1: 2 dS/m, S2: 4 dS/m, S3: 6 dS/m and S4: 8 dS/m), two betaine levels (B0: 0 mM and B1: 50 mM) and Nano fertilizer (N0: without Nano fertilizer and N1: with 3 mL/L Nano fertilizer) were arranged in a Randomized Complete Block Design (RCBD) with three replicates. Data for chemical properties were recorded. The results were analysed using One-way analysis of variance (ANOVA) followed by Duncan post-hoc test. B1N1 improved NO3 - and pH of sweet corn and A. thaliana, EC and Ca2+ of sweet corn and A. thaliana, respectively. Therefore, it is anticipated that B1N1 could reduce salt stress by improving the chemical properties in sweet corn as well as in A. thaliana.